Evaluasi Evaluasi Profitabilitas BCA Syariah melalui Rasio NIM 2020-2024 - hidayatullah, Moh. bayu; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study aims to evaluate the profitability of BCA Syariah by analyzing the Net Intermediation Margin (NIM) during the period 2020 to 2024. NIM is used as a key indicator to assess the bank’s effectiveness in managing productive assets and generating margin income from intermediation activities. The research applies a descriptive statistical approach using annual financial statement data of BCA Syariah. The results indicate that NIM experienced fluctuations, with a notable increase in 2021 and 2022 as the economy began to recover after the COVID-19 pandemic. However, a gradual decline occurred in 2023 and 2024 due to the rapid growth of productive assets that was not fully matched by the increase in margin income, along with tighter industry competition and rising cost of funds. Despite this decline, the NIM level remains within the fairly healthy to healthy category, reflecting the bank’s stable performance in maintaining its intermediation function. These changes are influenced by internal factors such as operational efficiency, funding structure, and financing quality, as well as external factors including macroeconomic conditions and financial industry dynamics. Overall, BCA Syariah demonstrates the ability to sustain its profitability while continuing to adapt to economic pressures and competitive challenges.